Workplace conflict and willingness to cooperate: The importance of apology and forgiveness. Issue 2 (11th April 2016) - Ayoko, Oluremi Bolanle
Abstract : Purpose: This paper aims to clarify the relationship between conflict, apologies, forgiveness and willingness to cooperate after a conflict event. Design/methodology/approach: The paper used scenarios and quantitative measures to examine the connection between conflict, perceived apology sincerity, forgiveness and willingness to cooperate in 358 business undergraduates. Findings: Data revealed that relationship conflict was significantly but negatively associated with forgiveness and willingness to cooperate. Additionally, attitudes toward forgiveness were directly and positively related not only to forgiveness but also to willingness to cooperate. Finally, forgiveness mediated the link between both perceived apology sincerity attitudes to forgiveness and willingness to cooperate. Research limitations/implications: Data were cross-sectional and may be subject to bias. Longitudinal studies are needed to further tease out the connection between the variables in the current study. Similarly, future research should explore the role of climate and individuals' disposition and readiness to apologize, forgive and their willingness to cooperate at work. Practical implications: The paper includes practical implications for managers interested in eliciting cooperation after a workplace conflict. Specifically, apology and forgiveness should be included in managers' conflict management training programs. Social implications: Our findings indicated that apology and forgiveness are social skills that are important for conflict management and cooperation after a workplace conflict. Originality/value: Beyond reconciliation, the current study provides new insights into the important role of actual forgiveness in whether employees are willing to cooperate after conflict at work. Practical assistance is offered to managers who are interested in fostering cooperation and increased performance after conflict episodes.